Springback analysis of thin tubes with arbitrary stress-strain curves / Mayank Gangwar … [et al.] - Gangwar, Mayank; Choubey, Vikas Kumar; Dwivedi, J. P.; Das Talukder, N K. (UiTM Press, 2011)
A general theoretical method for determining springback of arbitrary shaped thin tubular section of materials having arbitrary stress-strain relationship under torsional loading is presented. The theoretical analysis has been compared with earlier analysis of tubular sections of particular materials and has been shown that the expressions obtained in the, work presented. The theoretical results also have been found to quit in agreement with the results obtained experimentally. It has been shown that when applied torque is kinetic loading or angle of twist given is kinetic loading, springback angle and residual angle of twist can directly.